Czyn współukarany na przykładzie przestępstwa prania pieniędzy z art. 299 § 1 k.k. - Płońska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The author in this paper points out a very important issue of co-sanctioned acts in the context of one of the most serious white collar crimes, which is money laundering under Article 299 § 1 of the Criminal Code. The author indicates interpretational difficulties related to the concepts of prior co-sanctioned acts and consequent co-sanctioned acts. She also points out the prerequisites of the adoption of co-sanctioned act structure. After an analysis of money laundering crime under Article 299 § 1 of the Criminal Code, the author states that due to the teleological problem, it is not possible to adopt the co-sanctioned acts structure to all money laundering crimes within an abstract level. The design of a co-sanctioned act might be accepted for money laundering offence, but only after taking into account all the circumstances of the particular case.
Keywords: pranie pieniędzy; czyn współukarany; korzyść z przestępstwa; przestępstwo z art. 299 § 1 Kodeksu karnego